Synthesis, Anti-tumor Activity and Odd–even Effect of Simple Isatin Derivatives - Chen, Gang; Hao, Xiaojiang; Wang, Ye; Mu, Shuzhen (Letters in Drug Design & Discovery, 2015)
In this work, a series of N-substituted isatin derivatives was synthesized by different reactions. The synthesized isatin derivatives were characterized by NMR, MS and elemental analysis. Then the anti-tumor activities of these compounds were evaluated through the cytotoxicity against A549 and P388 cell line test. The results show that several compounds show much higher anti-tumor activity than that of isatin, and there is an even-odd effect in the structure activity relationship.
Keywords: Isatin